Experimentation and simulation of thermal energy storage system with non-phase change materials - Soontornchainacksaeng, Thanakom (Strojniški vestnik, 2005)
This research a simulation study and experiment on the thermal energy storage system with non-phase change materials in the range of 50° - 150°C, this system is consisted of the storage tank size of 0.58 m in diameter, and 0.88 min height, containing each set of the charging coil, and the discharging coil, embedded in the combination of 90% by volume of the used - engine oil, and 10% by volume of the river - water rocks. An electric heater is used as the heat source. The simulation of thermal-energy storage system with the mathematic modeling for the theoretical analysis of the system, and by using the Newton - Raphson method in the simulation process during the energy charging and discharging processes, The limitation of the charging oil temperature is maintained at 140°C with the flow rate in the range of 10 to18 l/min, whereas the inlet temperature of the discharge oil is maintainedat 30°C with the flow rate of 6 to 14 l/min. The computer simulation results with the charging time of 2 hours, and the oil flow rate of14 l/min, The temperature of our storage media is increased by 60°C with theamount of heat gain by 23 MJ. And by our further simulation on dischargingfor 1 hour period, with the oil flow rate of 10 l/min, the storagetemperature is decreased by 58°C, with the amount of heat removal of 23MJ. It is found that results from the experiment are differed from the simulation by 3-5 %.
Keywords: prenos toplote; energija toplotna; shranjevanje energije; hranilniki toplote; matematični modeli; simulacije